The influence of plautus in spain before Lope de Vega : together with chapters on the dramatic technique of Plautus and the revival of Plautus in Italy - Grismer, Raymond Leonard (New York: Hispanic Institute, 1944)
The drama of modern Europe bigins in 1486 with the presentation of the Menaechmi of Plautus, translated into Italian, before Ercole I in the corte Vecchia al Ferrara. From that date the preodominating influence on the European stage was the increasing number of Latin plays presnted in the original, in vernacular translations, or in adaptations according to local conditions.
Keywords: Vega, Lope de, 1562-1635; Comedia; Literatura